Light railways for the United Kingdom, India and the colonies a practical handbook, setting forth the principles on which light railways should be constructed, worked and financed, and detailing the cost of construction equipment, revenue and working expenses of local railways already established in the above-mentioned countries, and in Belgium, France, Switzerland, etc - Mackay, John Charles (Crosby Lockwood, 1896)
Promoting the virtues of light railways, this is a complete and practical handbook to the construction of same with many examples from around the world.